Black sun of melancholy: Landscapes of light and darkness in the poetry of José Verón Gormaz (XXI Century. Spanish Literature and Culture, 2024)
This paper examines the originality of José Verón Gormaz’s poetry in relation to its historical and literary context by analyzing a selection of nine poetry books and focusing on phenomena such as intertextuality and intermediality. The melancholic ethos as the dominant aesthetic procedure drives his poetry towards an anti-mystical, anti-metaphysical and anti-pure lyricism, with inversion as the main stylistic axis
Keywords: José Verón Gormaz; lyrics; melancholic ethos; anti